Recent Changes in Mid-latitude Wave Propagation - Attema, Ronnie (UiT Norges arktiske universitet, 2024)
In recent years climate change in the polar areas has attracted a lot of attention. Not only for its consequences in polar areas, but also for its possible effects on lower latitudes. A reduced temperature gradient between the polar areas is expected to weaken the mid-latitude jet stream. This weaker jet stream is hypothesised to lead to a reduction in the propagation velocity of atmospheric Rossby waves and lead to more persistent weather. In this study we will investigate these changes in wave propagation by computing the wave activity and wave activity flux from the ERA5 reanalysis for the time period 1990- 2020. We find that there are significant changes in the wave activity and wave activity flux, but not in the wave forcing of the mean flow. We find a seasonal and geographic dependency for the trends in the wave activity and its flux. We furthermore provide evidence that these changes can be linked to low sea ice concentrations. In addition we explore the relationship between the wave activity and the temperature. For this we find that a high wave-activity in general results in a negative temperature anomaly, but during the winter a high wave-activity is related to a positive temperature anomaly for some areas.